Penerapan Kepemimpinan Pastoral Yesus Kristus Dalam Kitab Injil Bagi Sekolah Tinggi Teologi Pelita Dunia - Adi Putra; Gunar Sahari (Sekolah Tinggi Teologi Arastamar Bengkulu, 2021)
This research discusses the pastoral leadership of Jesus Christ as written in the Bible to be applied in the Pelita Dunia Theological Seminary. So that every graduate produced can understand and practice correct pastoral leadership in accordance with the teachings and actions of Jesus Christ. This study uses a qualitative approach that combines a literature review with the results of interviews with several alumni. Through this research, information was obtained that Jesus' pastoral leadership based on the explanations in the Gospels is clearly visible in three ways, as Jesus' pastoral leadership carries out God's vision and that means that every pastor also carries out God's vision, Jesus' pastoral leadership reaches out to the lost and improves relationships and that means every pastor also reaches out to the lost congregation and mends broken relationship with God, and pastoral leadership Jesus disciplines and sends and that means every pastor disciplines and sends the congregation to preach the gospel. In addition, this study also concluded that Pelita Dunia Theological Seminary should include and teach Pastoral Leadership to every student in order to produce graduates who can serve like Jesus.